Advancing Improvements to Enterprise Systems with a Participatory System Dynamics Method Using Figma - Hussain, H.; de Vries, M. (The South African Journal of Industrial Engineering, 2025)
System dynamics (SD) offers a whole-system perspective to model complex, non-linear behaviour and to assess the impact of interventions in multiple performance areas. To address the difficulties of ill-defined SD concepts, a meta model for enterprise systems dynamics (MMESD) was previously developed and refined, resulting in the e1MMESD. This study applied the e1MMESD in a participatory system dynamics method (PSDM), enabling stakeholders collaboratively to build knowledge, manage uncertainty, and identify leverage points for system improvement. The PSDM, developed as a design science research artefact, is structured in four phases, and developed using the Figma modelling tool to support online collaboration. A single application of the PSDM resulted in both causal loop diagrams (CLDs) and causal loop stock and flow diagrams (CLSFDs) as final deliverables. The diagrams were tested and refined in workshops with five projects in agriculture, healthcare, manufacturing, and industrial services. The findings indicate that the proposed participatory method offers a flexible, replicable approach to improving an enterprise system, while providing valuable insights into how participatory practices could foster system understanding and the effect of suggested interventions.